PENGEMBANGAN MEDIA POWTOON PADA MATERI KERAGAMAN SOSIAL BUDAYA DI INDONESIA UNTUK SISWA KELAS 5 SD NEGERI DUDUKLOR - Rita Nakashifa Shohib; Nanang Khoirul Umam (Nusantara Hasana Journal, 2024)
The development of Powtoon media on socio-cultural diversity material in Indonesia for 5th grade students of SD Negeri Sitting Lor aims to determine the effectiveness, validity, and responses received by students. In this study, the development of learning media uses the ADDIE model which has 5 stages of development, namely Analysis, Design, Development, Implementation, Evaluation. In the analysis stage, the analysis used is media validity analysis, media effectiveness analysis, and student response analysis. The effectiveness analysis is carried out by means of media testing to students, distributing student response questionnaires and using an assessment of media and material validation which will later be assessed directly by media and material experts. The results of the final assessment given to Powtoon media experts on socio-cultural diversity in Indonesia are 95% and 85%, the media developed by researchers is categorized as very valid and feasible to be applied in classroom learning by media experts. the effectiveness of the media is assessed from the results of student responses and trials using 3 learning models, namely the question and answer learning model, inquiry and kooperatif STAD type. The assessment using the question and answer model obtained 95.2% results in the very good category, the assessment using the Inquiry model obtained 85.7% results in the very good category, and the assessment using the STAD Kooperatif model obtained 91.4% results in the very good category. good. So that this Powtoon media can be applied and used in the learning process in the classroom on the condition that it sees the suggestions and comments given by the validators so that the learning media becomes the perfect medium